A Critical Analysis of the Prosecution of Sexual and Gender-Based Violence at the International Criminal Court - Oyewole, Oriola O. (ABUAD Law Journal, 2023)
The prosecution of crimes of Sexual and Gender-Based Violence (SGBV) has remained a challenging issue for international criminal justice. Given that in the past, crimes of sexual violence within the context of international armed conflict were not considered substantive crimes. This is evidenced in the non-prosecution of sexual and gender-based crimes at the Nuremberg and Tokyo tribunals despite the incontrovertible utilisation of the "comfort women system" in Tokyo during World War II. However, with the emergence of the International Criminal Court(ICC), there seems to be a reasonable but piecemeal progression of the investigation and prosecution of SGBV. Although, previous studies have reported that investigating and gathering evidence for SGBV is a continuing concern within the jurisprudence of the ICC. The recently decided cases at the Court especially demonstrate a development and dynamics in the prosecution of SGBV at the ICC. By employing a doctrinal research method, I spotlight the nuances and hurdles of sexualised crimes within the ICC. The author recommends gender mainstreaming in the investigation and prosecution of sexual violence in order to fill the gap.